Robson Classification and quality audit - Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2021)
World Health Organization has recommended Robson Classification from baseline obstetric characters to assess, monitor and compare Cesarean Section rates by the quantity analysis. Incorporation of real time labor related factors requires quality audit for both maternal and perinatal outcome.